Kościelny "modus procedendi" w przypadkach pedofilii - Wytrwał, Tomasz (Prawo Kanoniczne, 2009)
In ancient Greece and in the countries of the East paedophile activities were, generally, not prosecuted; they were considered to be normal sexual practices. The Church saw this issue differently and, from the very beginning, condemned paedophilia. The earliest Church documents bear witness to that: Didache (ca 100), St. Justin condemns it in his Apologia (ca 153), Synod of Elwira (305-306), Apostolic Constitutions (ca 380), Gratian’s Decretum (ca 1140), the third Lateran Council (1179), the fourth Lateran Council (1215), the Code of Canon Law of 1917, and the Code of Canon Law of 1983. Paedophilia is a sexual deviation when an adult experiences sexual gratification only in relations with children that have not yet developed secondary and tertiary sexual features. According to the International Classifications of Diseases ICD-10, and according to the classification of the American Psychological Association DSM-IV, paedophilia belongs to the disturbances of sexual preferences. Paedophilia may take various forms: with or without the physical contact, with or without the use of force, it can also take the form of child’s pornography. According to can. 1395,2 of the Code of Canon Law the following are the distinctive elements that make up the crime of paedophilia: a) the age of the victim (below the age of eighteen) b) t he sexual nature of the offense against the sixth commandment of the Decalogue; c) the perpetrator must be a cleric. The Church’s Modus Procedendi stipulates that in cases of the molesting of minors, in the light of the Code of Canon Law of 1983 and of the EPISTULA a Congregatione pro Doctrina Fidei missa ad totius Catholicae Ecclesiae Episcopos aliosque Ordinarios et Hierarchas interesse habentes: DE DELICTIS GRAVIORIBUS eidem Congregationi pro Doctrina Fidei reservatis of 18th May 2001, the ecclesiastic superior must be notified of the likelihood of an offense having been committed. He conducts the preliminary investigation of which he, then, notifies the Congregation for the Doctrine of the Faith. The Congregation for the Doctrine of the Faith, having studied the findings of the preliminary investigation conducted by the ecclesiastic superior, issues him with an instruction as to the further proceedings. In the Church, the prosecution in cases of the molesting of minors terminates when ten years have lapsed since the victim came of age.